Does cellular elastic modulus change due to subculture and fixation: an atomic force microscopy study of nucleus pulposus cells in vitro - Xiao, Bowei; Zhou, Tianchi; Huang, Juying; Rong, Tianhua; Wu, Bingxuan; Liu, Baoge (European physical journal plus, 2023)
Cervical spinal degenerative disease (CSDD) is the progressive deterioration of cervical intervertebral disk (IVD) and is strongly related to the degeneration, necrosis, and apoptosis of nucleus pulposus cells (NPCs). The cellular mechanics of cervical NPCs is essential for the biomechanics of degenerative IVD and the pathogenesis of CSDD. Atomic force microscopy (AFM) can be used to quantify the cellular morphology and mechanics. However, the cellular subculture and experimental conditions may influence the cellular elastic modulus of the NPCs. In this study, cervical nucleus pulposus cells were cultured in vitro and their cellular elastic modulus were measured using AFM to explore the influence of cell subculture and cell fixation on the elastic modulus. To this end, the cellular morphology and mechanical properties of the HNPCs were successfully quantified by AFM. The elastic modulus of the primary NPCs was maintained with P2 generation (2 passages in vitro) cells during the in vitro culture and the elastic modulus increased after fixation. The results of this study lay the foundation for further research. P2 generation, living NPCs are recommended as the experimental subject for exploring the cellular mechanics mechanisms of cervical degenerative disease.